PENYALURAN, PENGENDALIAN DAN PENGAWASAN SEMBILAN BAHAN POKOK - Wahyu Subono (Jurnal Manajemen FE-UB, 2019)
At present the distribution and control of all nine staples given to this market mechanismhas taken place since the reformation in 1998, and in the history of Indonesia has had acontrolling body of nine staples since in the Indies under the name Voedings Middelen Fonds(VMF) in 1939 specifically rice.When the second President of the Republic of Indonesia, Soeharto, was formed andinaugurated BULOG (Logistics Affairs Agency) on May 10, 1967.Through Presidential Decree No. 39/1978, President Soeharto decided that the main task ofBulog was to control the price of rice, grain, wheat and other staples in order to maintain pricestability,Both for producers and consumers according to government policyThe era of reform occurred when the 4th President Abdulrahman Wahid alias Gus Durruled, a Buloggate scandal occurred and since January 20, 2003 the status of Bulog wasformalized as a state-owned public company.In Law No. 8/2012 on Food is mandated that the government and the community areresponsible for realizing food security. This can be interpreted that food security is a marketmechanism such as some developed and liberal countriesThe National Logistics Agency is expected to be the supervisor, distribution and control ofthe nine staples for food security for special small communities and the general welfare of theIndonesian people in general.